Analysis of the regional dynamics of employment using a spatially modified Shift–Share model in the Great Metropolitan Area (GAM) of Costa Rica, 2000–2011 - Arias Ramírez, Rafael (2013)
This article is a result from a broader study on the patterns of concentration and evolution of the process of industrial localization and the labor market in the Great Metropolitan Area of Costa Rica (GAM). This study is part of the research program on regional economics that the Institute of Research in Economic Sciences of the Universidad de Costa Rica (IICE) has been conducting since the year 2005. The article is aimed to show an approximation to the regional dynamics of employment in the GAM in the period 2000-2011. In order to do that we applied the Shift-Share analysis in its classic and spatially modified formulations. This allows us to decompose employment growth in four effects: the national effect, the sectorial effect, the regional effect and the “locational” effect.